The Survival Strategies of Micro, Small and Medium Enterprises in the New Normal Era: Insight from Palembang - Fadil Azimuddin; Yunindyawati Yunindyawati; Sriati Sriati (Jurnal Studi Sosial dan Politik, 2023)
Adaptation Strategy for Pempek Business Actors During the Covid 19 Pandemic in Pempek Village 26 Ilir Palembang City which aims to understand and know adaptation strategy for Pempek businesses during the Covid 19 pandemic. Pempek Village 26 Ilir, Palembang City as a sample to identify adaptation strategies and constraints.Based on the theory of Ahimsa Putra, including Adaptive Behavior, Adaptive Strategies, Adaptive Processes. This research according to the type of data used is descriptive qualitative research with key informants, Pempek Business Actors in Pempek Village 26 Ilir Palembang City, Consumers or Buyers, totaling 17 people. The research instrument used in-depth interviews, literature study, documentation and observation.Based on the results of the research, first about adaptive behavior, Pempek business actors in Kampung Pempek 26 Ilir changed sales from conventional to online. The two adaptive strategies of Pempek business actors in Kampung Pempek 26 Ilir changed payments which were originally direct to virtual online, such as via bank transfers and OVO. The three adaptive processes, namely business actors reducing the amount of production so that business continuity can still survive during the Covid 19 pandemic. Then, the obstacles faced by business actorsPempek in Kampung Pempek 26 Ilirmake adjustments that refer to problems arising from the interdependence of all aspects of culture, where the covid 19 pandemic affects the economy which will inevitably affect the government to carry out large-scale restrictions or social distancing, business actors Pempek in Kampung Pempek 26 Ilir forced to adapt to situations faced by economic changes, forcing business actorsPempek in Kampung Pempek 26 Ilir adapt to environmental changes during the Covid-19 pandemic.